The Influence of Content Marketing, Online Customer Reviews, Live Streaming, and Flash Sales on Purchase Decisions of Ethica Seply Products at Bindawood Purwokerto TikTok Shop - Aulia Azzahra; Wisnu Wijayanto; Akbar Pahlevi (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The growth of TikTok Shop as a social commerce platform has transformed consumer purchasing behavior in the Muslim fashion industry, particularly through digital marketing strategies that integrate product information, real-time interaction, consumer-generated evaluations, and promotional incentives. This study aimed to examine the effects of content marketing, online customer reviews, live streaming, and flash sales on consumers’ purchase decisions regarding Ethica Seply products on TikTok Shop Bindawood Purwokerto. A quantitative approach with an explanatory research design was employed, involving 188 respondents selected through simple random sampling. Data were collected using questionnaires and analyzed through multiple linear regression. The findings indicate that content marketing, online customer reviews, live streaming, and flash sales each have positive and significant effects on purchase decisions. Among these variables, online customer reviews emerged as the most influential determinant, while the four variables collectively explained 67% of the variation in purchase decisions. The study concludes that integrated digital marketing strategies play a significant role in strengthening consumer purchase decisions in social commerce environments. These findings contribute to the literature on digital marketing and social commerce by demonstrating the combined influence of content-based, interaction-based, review-based, and promotion-based strategies on consumer behavior in the Muslim fashion industry. Practically, the study implies that businesses should optimize customer review management, improve content quality, enhance live streaming engagement, and design effective flash sale programs to strengthen consumer trust and engagement.